Wheel slip control of EVs based on sliding mode technique with conditional integrators - Ricardo de Castro (2013)
This paper presents a new control system, based on field programmable gate array technology, targeting the power-train control of multi-motor electric vehicles (EVs). The control chip builds around a reusable intellectual property core named propulsion control unit, which features motor control functions with field-orientation methods, and energy loss minimization of induction motors. In order to improve the EV safety, the control system was extended with a wheel slip controller based on the sliding mode framework. The robustness to parametric and modeling uncertainties is the main attraction in this design, thanks to a simple connection that was found between the driving torque request and the model uncertainty. To overcome the chattering issue, which arrives from the discontinuous nature of the sliding control, the conditional integrator approach was employed, enabling a smooth transition to a Proportional+Integral control law, with anti-windup, when the tire slip is close to the setpoint. The controller asymptotic stability and robustness was analytically investigated through the Lyapunov method. Experimental results, obtained with a multi-motor EV prototype under low grip conditions, demonstrate a good slip regulation and robustness to disturbances.